Alcohol and Bone Turnover Markers among People Living with HIV and Substance Use Disorder. (2nd March 2020) - Kim, Theresa W.; Ventura, Alicia S.; Winter, Michael R.; Heeren, Timothy C.; Holick, Michael F.; Walley, Alexander Y.; Bryant, Kendall J.; Saitz, Richard
Abstract : Background: Although unhealthy alcohol use and low bone density are prevalent among people living with HIV (PLWH), it is not clear whether alcohol use is associated with bone turnover markers (BTMs), and if so, at what quantity and frequency. The study objective was to examine the association between alcohol and BTMs in PLWH with substance use disorder. Methods: We studied a prospective cohort recruited from 2 HIV clinics who met criteria for DSM‐IV substance dependence or reported ever injection drug use. Outcomes were BTM of (i) bone formation (serum procollagen type 1 N‐terminal propeptide [P1NP]) and (ii) bone resorption (serum C‐telopeptide type 1 collagen [CTx]). Alcohol consumption measures included (i) mean number of drinks/d (Timeline Follow‐Back [TLFB]) (primary predictor), (ii) any alcohol use on ≥20 of the past 30 days, and phosphatidylethanol (PEth), a biomarker of recent alcohol consumption. Linear regression analysis examined associations between (i) each alcohol measure and each BTM and (ii) change in alcohol and change in BTM over 12 months. Results: Among 198 participants, baseline characteristics were as follows: The median age was 50 years; 38% were female; 93% were prescribed antiretroviral medications; 13% had ≥20 drinking days/month; mean drinks/day was 1.93 (SD 3.89); change in mean drinks/day was −0.42 (SD 4.18); mean P1NP was 73.1 ng/ml (SD 34.5); and mean CTx was 0.36 ng/ml (SD 0.34). Higher drinks/day was significantly associated with lower P1NP (slope −1.09 ng/ml; 95% confidence interval [CI] −1.94, −0.23, per each additional drink). On average, those who drank on ≥ 20 days/month had lower P1NP (−15.45 ng/ml; 95% CI: −26.23, −4.67) than those who did not. Similarly, PEth level ≥ 8ng/ml was associated with lower P1NP. An increase in drinks/d was associated with a decrease in P1NP nonsignificantly (−1.14; 95% CI: −2.40, +0.12; p = 0.08, per each additional drink). No significant associations were detected between either alcohol measure and CTx. Conclusions: In this sample of PLWH with substance use disorder, greater alcohol consumption was associated with lower serum levels of bone formation markers. Abstract : We examined whether alcohol consumption was associated with serum bone turnover markers in a sample of adults with HIV infection and a substance use disorder. Alcohol exposure was examined with three self‐report measures of past month alcohol quantity/frequency as well as phosphatidylethanol (PEth) level, a biomarker of recent alcohol consumption. All alcohol consumption measures were associated with lower levels of a bone formation marker (P!NP) but not with C‐telopeptide, a marker of bone resorption. Vitamin D deficiency was not a mediator in these associations.